Dreamquake : Book Two of the Dreamhunter Duet - Knox, Elizabeth (New York : Frances Foster Books, 2007)
Aided by her family and her creation, Nown, Laura investigates the powerful Regulatory Body's involvement in mysterious disappearances and activities and learns, in the process, the true nature of the Place in which dreams are found.
The isle of the temple -- Foreigner's north -- Summer and Christmas -- The depot -- The gate -- Epidemic contentment -- Lazarus Hame.
Originally published: London : Faber & Faber, 2007.
Keywords: Dreams -- Fiction; Family life -- Fiction; Fiction